Financial and political aspects of state intervention in the British film industry, 1925-1939 - Street, S; Street, Sarah (1985)
﻿ During this period the state's interest in the film industry took several different forms. The area of films policy explored in this thesis is the economic protection of the commercial film industry against the high percentage of American films screened in Britain and the Empire. I begin in 1925 because it was not until then that active steps were taken by the government, in response to agitation from producers and those who saw film as a bond of Empire and advertisement for British goods and 'way of life', leading to the Cinematograph Films Act, 1927. This proposed, for political, cultural, moral and economic reasons, that renters and exhibitors should acquire and show a percentage of British films. There was no subsidy for producers or a heavy duty levied on American film imports. The origins, impact and character of official film policy are explored in the thesis with particular attention to financial and political aspects. An attempt is made to explain why policy was limited to film quotas together with an assessment of their impact on the industry's economic development. Details are also given on how the film industry's affairs became caught up in wider debates on tariff policy in the 1920s and in Anglo-American relations ten years later. The first three chapters deal with the evolution, promulgation and initial impact of the Cinematograph Films Act, 1927. Chapter 4 examines the deliberations of the Moyne Committee, established in 1936 to review the film industry's progress. The last three chapters analyse the three major influences on policy during the making of the 1938 Films Act: the campaigns of British film trade interests; the state of Anglo-American relations and film finance. In the final assessment the major influences that shaped policy are outlined together with conclusions on the industry's position and problems on the eve of the Second World War.